Synthesis and Characterization of Novel Bis-Arsenic Complexes - Arabuli, L.; Matoga, D.; Lekishvili, N. (Asian Journal of Chemistry, 2011)
p-Phenylenebis[diethyl(iso-propyl)arsonium] tetra-N-thiocyanatocobaltate(II) cationic-anionic complex have been synthesized and studied. The X-ray structure of +[(i-Pr)2(Et)4As2(Ph)]+ [Co(NCS)4]2- have been determined. Crystals belong to the tetragonal system, space group P-42(1)m) with a = 14.4930(14)Å, b = 14.4930(14)Å, c = 8.7090(19)Å; α = 90°, β = 90°, γ = 90°. The structures were refined to an R value of 0.063 from 4082 observed reflections. The As atom is coordinated tetrahedraly to the substituents as well as the anion has a tetrahedral configuration. The synthesis and IR spectral characterization of the complex compounds are described.